Editorial Volume 4, Issue 3 - Ciorstan J. Smark (Australasian Accounting, Business and Finance Journal, 2010)
This issue of AABFJ presents papers from a range of approaches and research topics in keeping with the journal’s broad focus on accounting, finance and business. This issue includes the examination of micro-structure finance in the context of real estate pricing and an analysis straddling financial analysis and the role of accounting standards in decision-making. The policing paper in accounting employs a social constructionist approach to the study of the New Zealand public sector. Business education is represented in a study of students undertaking internships as part of their university degree in commerce. In the last issue, the editors flagged the move to broaden the scope of the journal to include shorter articles and book reviews. This issue presents the first book review. Readers will no doubt notice that the printable Research Online format has returned to A4. In an environment of resource constraints, both financially and environmentally, the editors decided that the revised format is more appropriate. As usual, electronic media is the most prevalent mode of delivery.